Peran Ustadz sebagai Otoritas Ontologis dalam Pembentukan Akhlak Santri Tsanawiyah (SMA) di Pesantren Imam Bukhari - Mujiburrohman, Mujiburrohman; Permatasari, Indah Gilang (Lembaga Yasin AlSys, 2026)
Moral education is the core of Islamic education, aimed at shaping noble human character, and within the pesantren context the ustadz functions not only as a religious instructor but also as an ontological authority who serves as a reference point for the truth of practice and as a life model for santri. This study aimed to analyse the role of ustadz as an ontological authority in shaping the moral character of santri at the tsanawiyah level of Pondok Pesantren Imam Bukhari. A qualitative approach with a field study design was employed, using observation, in-depth interviews, and documentation to reveal the contextual practice of moral education. The findings show that ustadz possess ontological authority manifested through moral exemplarity, spiritual depth, behavioural consistency, and academic as well as religious legitimacy. The process of character formation among santri takes place through the internalisation of tauhid values, habituation of worship, continuous supervision, and educational relationships grounded in ethical principles. This study affirms that an ontological approach to the role of ustadz strengthens the effectiveness of moral education in pesantren and is relevant as a model for the development of moral education in Islamic educational institutions.